Microwave-Assisted, One-Pot Three Component Synthesis of 2-Phenyl H-imidazo[1, 2-α]pyridine. Issue 3 (2012) - Motevalli, Kourosh; Yaghoubi, Zahra; Mirzazadeh, Roghieh
Abstract : A novel synthesis of 2-phenylH-imidazio[1, 2-α] pyridines is described from a one-pot, three-component reaction between pyridine, guanidine (urea or thiourea) and α-bromoketones under microwave irradiation and solvent-free conditions in excellent yields.